Climate Change in School Geography Textbooks (Spain) in the Era of the ICTs: Perception and Teaching According to Teachers - Álvaro-Francisco Morote; María Hernández-Hernández (MDPI AG, 2023)
Climate change has become one of the major themes in the academic world, as it constitutes a socio-environmental challenge faced by society in the twenty-first century. The objectives of this study, based on the opinions of geography teachers (secondary education and baccalaureate, Spain), were to analyze the frequency of use of school textbooks in geography classes, to examine how climate change is addressed in these resources, to study how teachers impart these contents, and to review the importance of teaching global warming according to the opinions of the teachers. Based on a sample of 96 teachers surveyed between 2019 and 2022, the results show a disparity of opinions regarding textbook use, a not-altogether-adequate treatment of this phenomenon with these resources (the sum of the responses with values of 1 and 2 amounted to 44.8%), and a predominance of an explanation of climate change by teachers through everyday cases in the students' environment (35.4%) and talks and workshops given in class by experts (27.1%). Knowing the use made by teachers of the traditional textbook in the era of the ICTs, their perception of the adequacy of the contents on climate change in these resources, and how this phenomenon is taught is highly relevant to raising awareness and educating the youngest cohorts about one of the main challenges faced by society today.